Akshara Divāḷī, 1985 - Ināmadāra-Sāne, Rekhā.; Parāñjape, Pra. Nā.; Bhāve, Sa. Śi. (Mumbaī : Mêjesṭika Prakāśana, 1986)
Anthology of fiction, articles, essays, poems, etc., selected from the Divali issues of Marathi periodicals published in 1985.
In Marathi.
Mode of access: Internet.
Keywords: Marathi literature -- 20th century